(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In this study, adsorption of different monobasic and dibasic acids was performed on Walnut shell carbon,which was used as an adsorbent, asit is serves as eco-friendly adsorbents. It has proven to be significantly effective with the provision of satisfactory adsorption capacities for the removal of pollutants from waste water. We have studied adsorption on different monobasic and dibasic acid by taking Walnut shellcarbon as an adsorbent. The monobasic acids and dibasic acids under study were Acetic acid, Propionic acid, oxalic acid and Succinic acid.Walnut shell is the best materialthatcanbemadeintocarbonasthey have a lot of micropores, low ash content high water Solubility and high reactivity.Walnut shellcarbon has become one of the best forms of carbon for waterfiltration and water Purification in recent years. Additionally, it can effectively absorb Certain impurities.